Dealing with the Challenges of Macro Financial Linkages in Emerging Markets - Canuto, Otaviano; Ghosh, Swati R. (Washington, DC: World Bank, 2013)
The 2008 financial crisis has highlighted the challenges associated with global financial integration and emphasized the importance of macro financial linkages. In the financial sector, attention is being directed toward macro prudential regulations that are geared toward the stability of the financial system as a whole. The Third Basel Accord (Basel III) aims to dampen the pro-cyclicality of the financial sector and to reduce cross sectional systemic risks partly by introducing measures to address liquidity and issues of banks being too big to fail. In the macro arena, the facts that price stability was not sufficient to guarantee macroeconomic stability and that financial imbalances developed despite low inflation and small output gaps have highlighted the need for additional tools (macro prudential policies) to complement monetary policy in countercyclical management. Emerging markets face different conditions and have key structural features that can have a bearing on the relevance and efficacy of the measures. The chapters in this volume discuss the challenges of dealing with macro financial linkages and explore the policy toolkit available for dealing with systemic risks with particular reference to emerging markets. This report is organized as follows: chapter one is adapting macro prudential approaches to emerging and developing economies; chapter two is adapting micro prudential regulation for emerging markets; chapter three presents capital flow volatility and systemic risk in emerging markets: the policy toolkit; chapter four presents monetary policy and macro prudential regulation: whither emerging markets; chapter five deals with macro prudential policies to mitigate financial vulnerabilities in emerging markets; chapter six presents sailing through the global financial storm; and chapter seven presents operation of macro prudential policy measures.